Peptide of Trichinella spiralis Infective Larval Extract That Harnesses Growth of Human Hepatoma Cells - Ruenchit, Pichet; Reamtong, Onrapak; Khowawisetsut, Ladawan; Adisakwattana, Poom; Chulanetra, Monrat; Kulkeaw, Kasem; Chaicumpa, Wanpen (Frontiers in Cellular and Infection Microbiology, 2022)
Trichinella spiralis, a tissue-dwelling helminth, causes human trichinellosis through ingestion of undercooked meat containing the parasite’s infective larvae. However, benefits from T. spiralis infection have been documented: reduction of allergic diseases, inhibition of collagen-induced arthritis, delay of type 1 diabetes progression, and suppression of cancer cell proliferation. Since conventional cancer treatments have limited and unreliable efficacies with adverse side effects, novel adjunctive therapeutic agents and strategies are needed to enhance the overall treatment outcomes. This study aimed to validate the antitumor activity of T. spiralis infective larval extract (LE) and extricate the parasite-derived antitumor peptide. Extracts of T. spiralis infective larvae harvested from striated muscles of infected mice were prepared and tested for antitumor activity against three types of carcinoma cells: hepatocellular carcinoma HepG2, ovarian cancer SK-OV-3, and lung adenocarcinoma A549. The results showed that LE exerted the greatest antitumor effect on HepG2 cells. Proteomic analysis of the LE revealed 270 proteins. They were classified as cellular components, proteins involved in metabolic processes, and proteins with diverse biological functions. STRING analysis showed that most LE proteins were interconnected and played pivotal roles in various metabolic processes. In silico analysis of anticancer peptides identified three candidates. Antitumor peptide 2 matched the hypothetical protein T01_4238 of T. spiralis and showed a dose-dependent anti-HepG2 effect, not by causing apoptosis or necrosis but by inducing ROS accumulation, leading to inhibition of cell proliferation. The data indicate the potential application of LE-derived antitumor peptide as a complementary agent for human hepatoma treatment.